The influence of service quality and product quality on member satisfaction at the Mitra Pandawa Pilangsari Jatitujuh Producer Cooperative - Kusman, Maman; Sobariah, Ade; Pratiwi, Vina Andita (Institute of Accounting Research and Novation (IARN), 2024)
In a cooperative there are many factors that influence member satisfaction, including the quality of service and product quality in the cooperative. This research aims to determine the effect of service quality and product quality on member satisfaction. This research uses descriptive and verification methods. The population of this study were members of the Mitra Pandawa Pilangsari Producer Cooperative. The sampling technique uses purposive sampling. The number of respondents was 72 members. The research instrument used a questionnaire. The research results show that service quality and product quality have a positive and significant effect on member satisfaction. This is proven by the regression results Y = 1.039 + 0.310X1 + 0.462X2. This means that if the value of service quality and product quality is zero, then member satisfaction is worth 1.039. If product quality remains the same and service quality increases by 1 unit, member satisfaction increases by 0.310. If the service quality variable remains constant and product quality increases by 1 unit, member satisfaction increases by 0.462. The correlation value is 0.813, meaning that service quality and product quality have a very strong relationship with member satisfaction. Service quality and product quality contribute 33.9% to member satisfaction, while the remaining 33.9% is influenced by other variables not studied.